The Novel Quantitative Assay for Measuring the Antibiofilm Activity of Volatile Compounds (AntiBioVol) - Malwina Brożyna; Anna Żywicka; Karol Fijałkowski; Damian Gorczyca; Monika Oleksy-Wawrzyniak; Karolina Dydak; Paweł Migdał; Bartlomiej Dudek; Marzenna Bartoszewicz; Adam Junka (Applied Sciences, 2020)
Herein, we present a new test, dubbed AntiBioVol, to be used for the quantitative evaluation of antibiofilm activity of volatile compounds in vitro. AntiBioVol is performed in two 24-well plates using a basic microbiological laboratory equipment. To demonstrate AntiBioVol usability, we have scrutinized the activity of volatilized eucalyptus, tea tree, thyme essential oils, and ethanol (used for method suitability testing) against biofilms of Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans. We have also compared AntiBioVol with the standard disc volatilization method, placing a special stress on evaluating the impact of various technical parameters on the outcomes of the latter method. The obtained results indicate that AntiBioVol allows analyzing the antibiofilm activity of volatile compounds in a high number of repeats and provides semi-quantitative or quantitative results of high repeatability. In comparison to disc volatilization, AntiBioVol is a more space- and cost-effective method that allows analyzing various types of microbial aggregates. Moreover, we have indicated that the possible reasons for the discrepancies in the results obtained by means of the standard disc volatilization method may be related to various parameters of the testing dishes used (height, volume, diameter) and to various volumes of the agar medium applied. In turn, the application of a 24-well plate and a strictly defined AntiBioVol protocol provide a higher control of experimental conditions. Therefore, the application of AntiBioVol may enable an optimization of and introduction of volatile compounds to the fight against infective biofilms.